Physico-chemical and sensory evaluation of Bilimbi (Averrhoa bilimbi L.) powder as souring ingredient - Limbaga, Joyce C. (Journal of Human Ecology, 2014)
Bilimbi, commonly known as kamias, is an indigenous, underutilized fruit of the Philippines which is used as a souring ingredient in Filipino dishes such as sinigang and paksiw. Its fruit-bearing is seasonal, thus processing it into a dried powder from was realized to make it available year-round and minimize harvest losses. In this study, bilimbi was processed into powder to be used as souring ingredient in food. The powder was evaluated for its physico-chemical and sensory characteristics. Production recovery and cost of production were also determined. Hot air oven-drying was employed using two drying temperatures, 50°C and 60°C, to dry the slices of blanched and unblanced bilimbi fruits for 24 h. There was no significant change in pH, TSS and %TA of bilimbi when processed into powder. Results indicated that the use of 50°C drying temperature resulted in lighter, more green and yellow color of powder compared to using 60°C. The pH ranged from 2.6 to 3.1, TSS from 2.747% to 2.963°B, TA from 10.06 to 14.577%, solubility from 17.823 to 21.717%, moisture content from 5.325 to 11.30% and percent recovery from 4.75-5.39%. Production cost per gram powder was in the range of Php 1.93-2.25, based on prices as of November 2014. Sensory evaluation showed that the dilution used was too sour. The acceptability was in the range of dislike slightly to like moderately in the 9-point Hedonic scale.